A risk dispatching model with Muskingum constraints for cascaded hydro systems. Issue 8 (16th April 2018) - Ge, Xiaolin; Zhong, Junling; Xia, Nenghong; Jin, Yan
Abstract : A risk dispatching model for short‐term cascaded hydro scheduling during high‐water season is proposed in this paper taking into consideration of uncertainty factors and the process of water flow. The uncertainty of natural inflow and market price is simulated by the multi‐scenarios method. The conditional value at risk (CVAR) is introduced to quantify the risk caused by these uncertainties. In the objective function, the added CVAR represents the risk preference of the hydropower producer. Based on the degree of risk aversion of the producer, the generation profit and risk are coordinated. In addition, the Muskingum model is used to formulate the process of water flow between upstream and downstream stations. A mixed‐integer linear programming model of short‐term cascaded hydro system scheduling in the high‐water season is developed and solved. Numerical studies demonstrate that the proposed approach can balance the risk and generation profit in the high‐water season and the model with the Muskingum constraint is more refined. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.